Détermination de l’influence du trajet de déformation sur la courbe limite de formage - Thang, Nguyen Nhat (Vietnam Journal of Mechanics, 1996)
The aim of this study is to predict the strain path influence on the forming limit diagram, from the limit stress curve. We consider two types of path, composed of two straight segments corresponding to stretching-tension and tension-stretching sequences.